Judicial Detection Skill, Litigational Opportunism, and Contractual Compliance - Dieter Schmidtchen; Roland Kirstein (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1996)
Mutually beneficial agreements might fail if the parties fear contractual opportunism. Litigation is supposed to prevent this, but still leaves room for litigational opportunism: Even knowing that the opponent has fulfilled his obligations, a party might bring suit. We show that with positive judicial detection skill, litigation fees can be designed to deter opportunistic suits and simultaneously induce bilateral contractual compliance. With zero detection skill, as implicitly assumed by most of the economic literature on litigation, bilateral contractual compliance cannot be induced. We apply our results to evaluate the American and the British cost allocation rules. – – Beidseitig vorteilhafte Abkommen können scheitern, wenn eine der Parteien vertraglichen Opportunismus befürchtet. Gerichtsklagen sollen diesem Problem abhelfen, eröffnen aber eine Gelegenheit für Prozeß-Opportunismus: Selbst wenn eine Vertragspartei weiß, daß die andere ihre Leistungspflicht erfüllt hat, kann sie auf Leistung klagen. Wenn Richter positive Erkenntnisfähigkeit haben, dann können Gerichtskosten so festgelegt werden, daß die Parteien von opportunistische Klagen abgeschreckt und zu vertragsgetreuem Verhalten motiviert werden. Können Richter nicht zwischen legitimen und opportunistischen Klagen unterscheiden, dann kann beideseitige Vertragseinhaltung nicht angeregt werden. Wir wenden dieses Ergebnis an, um die amerikanische und die britische Gerichtskostenregel miteinander zu vergleichen.
Keywords: K12; K41; C72; 330; procedural law; frivolous suits; positive detection skill; verifiability; litigation costs; American rule; British rule